Adverse selection, risk sharing and business cycles - Marcelo Veracierto (Federal Reserve Bank of Chicago, 2014)
I consider a real business cycle model in which agents have private information about an idiosyncratic shock to their value of leisure. I consider the mechanism design problem for this economy and describe a computational method to solve it. This is an important contribution of the paper since the method could be used to solve a wide class of models with heterogeneous agents and aggregate uncertainty. Calibrating the model to U.S. data I find a striking result: That the information frictions that plague the economy have no effects on business cycle fluctuations.
Keywords: C63; C68; D31; D82; E32; 330; adverse selection; risk sharing; business cycles; private information; incentives; optimal contracts; computational methods; heterogeneous agents